Privatization as a Valid Alternative - Millett, Sawin (Maine Policy Review, 1993)
At the "Rethinking State Government" conference held at the University of Maine in January 1993, a panel explored the issue of privatization, of using private enterprise to provide public sector services. Sawin Millet provides the perspective of someone who has worked primarily in the public sector.
Keywords: privatization; Maine